2018
DOI: 10.18203/2394-6040.ijcmph20184578
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study to assess the functioning of cold chain in a tribal district of central India

Abstract: Background: Immunization is one of the best efforts that India is putting forward currently to fight against various vaccine preventable diseases. Cold chain maintenance is always an issue. Therefore, cold chain maintenance is a pre-requisite in the correct delivery of immunization services.Methods: A cross sectional study was conducted among 18 cold chain points (CCPs) of Jhabua district using standard Government of India (GOI) structured questionnaires.Results: Out of 18 cold chain points only 5.55% had dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
1
Order By: Relevance
“…In our study, we found more cataract cases. According to one study[ 22 ] conducted in central India, prevalence of diabetes was 19.5% and of hypertension was 31.7%, not matching our findings. Fichter JH[ 23 ] also conducted a study on catholic priests and their health status.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, we found more cataract cases. According to one study[ 22 ] conducted in central India, prevalence of diabetes was 19.5% and of hypertension was 31.7%, not matching our findings. Fichter JH[ 23 ] also conducted a study on catholic priests and their health status.…”
Section: Discussioncontrasting
confidence: 99%